The Predictive Value of Serum Inflammatory Factors High-sensitivity C-reactive Protein Combined with High Level of Lipoprotein-associated Phospholipase A2 for the Onset of Ischemic Stroke: serum Lp-PLA2, MPO, serum ferritin in Ischemic Stroke - Zuo, Yaojin (Journal of Medical Biochemistry, 2025)
Objective: the aim of this article was to carried out an exploration of the predictive value of serum high-sensitivity C-reactive protein (hs-CRP) plus high levels of lipoprotein-associated phospholipase A2 (Lp-PLA2) for the onset of ischemic stroke (IS). Material and Method: 526 IS patients were selected as the experimental group (EG). During the same period, 463 healthy individuals served as the control group (CG). The levels of Lp-PLA2, myeloperoxidase (MPO), total cholesterol (CHO), low-density lipoprotein cholesterol (LDL-C), triglyceride (TG), hs-CRP, and serum ferritin (SF) in the serum of subjects were compared. The predictive efficacy of combination of two for the onset of IS was assessed. Result: the levels of Lp-PLA2, MPO, CHO, LDL, TG, hs-CRP, and SF in patients with IS were all markedly higher as against the CG (P<0.05). Multivariate Logistic regression analysis (MLRA) suggested that both hs-CRP and Lp-PLA2 were independently associated with the risk of IS (OR=1.334, 95%CI=1.713 1.954; 1.251, 1.011 1.921). The ROC curve analysis revealed that the predictive efficacy for IS of hs-CRP in combination with Lp-PLA2 (area under the ROC curve (AUC)=0.786) was markedly better as against hs-CRP alone (0.713) or Lp-PLA2 alone (0.698) (P<0.05). Conclusion: serum hs-CRP in conjunction with elevated Lp-PLA2 levels demonstrated obvious predictive value for IS, aiding in the early identification of high-risk groups.